2015
DOI: 10.1097/md.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 rs1927911, but Not TLR2 rs5743708, Is Associated With Atherosclerotic Cerebral Infarction in the Southern Han Population

Abstract: The objective of this study was to explore the association of toll-like receptor (TLR) 4 rs1927911 and TLR2 rs5743708 with atherosclerotic cerebral infarction (ACI) and their effects on blood pressure, fasting blood glucose, and blood lipids in the Han population of Hunan Province.TLR4 rs1927911 and TLR2 rs5743708 were detected by polymerase chain reaction and restriction fragment length polymorphism in 170 patients with ACI and 149 healthy controls.Our results indicated that the genotype and allele frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Rs1927911 had been reported to be associated with T2DM in southern Chinese (Peng et al, 2015). The rs1927911 polymorphism of the TLR4 gene may be a risk factor for atherosclerotic cerebral infarction (ACI) in the Southern Han population of Hunan Province (Song et al, 2015). However, it may not be associated with fasting blood sugar (Song et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rs1927911 had been reported to be associated with T2DM in southern Chinese (Peng et al, 2015). The rs1927911 polymorphism of the TLR4 gene may be a risk factor for atherosclerotic cerebral infarction (ACI) in the Southern Han population of Hunan Province (Song et al, 2015). However, it may not be associated with fasting blood sugar (Song et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The rs1927911 polymorphism of the TLR4 gene may be a risk factor for atherosclerotic cerebral infarction (ACI) in the Southern Han population of Hunan Province (Song et al, 2015). However, it may not be associated with fasting blood sugar (Song et al, 2015). Also, there was no direct relation between rs1927911 and diabetes among the Germans (Kolz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Results of a study conducted by Yanmin Song et al in the southern Chinese province of Hunan in 2014 showed that for rs1927911 there is a meaningful difference between acute cardiac ischemia (ACI) patients and the control groups from a genotype and allele distribution but hypertension, fasting blood sugar and serum fat level with different genotypes in both ACI patients and control groups had no meaningful difference (20).…”
Section: Discussionmentioning
confidence: 99%